Comprehensive medication management: Review and recommendations for quality measures. Issue 4 (18th February 2023) - Haas, Curtis E.; Kliethermes, Mary Ann; Armistead, Lori T.; Beavers, Craig; Schumacher, Christie; Smith, Lisa; Armitstead, John A.; Emmons, Roshni P.; Darakjian, Lucy; Edwards, Krystal L.; Barr, Michael; ,
Abstract: Comprehensive medication management (CMM) provided by a clinical pharmacist can improve the quality of care and reduce health care costs through the optimization of medication use and a significant reduction in medication‐related problems. As demonstrated by multiple research studies and detailed in published use cases, CMM should be an essential practice for improving population health. This narrative review discusses the limitations of the current evidence and recommends structure, process, and outcome measures to ensure that the key elements of CMM that drive the observed benefits are implemented with fidelity to address the goals of the quadruple aim. The proposed outcome measures are further sub‐classified into economic, clinical, and humanistic categories. Several medication‐related measures are recommended to help define the importance and value of CMM as a key component of population health management.